FACTORS INFLUENCING THE UTILIZATION OF REGIONAL TOURISM - Anvarova Muhsinakhon Otabek kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article examines the key factors influencing the utilization of regional  tourism  and  their  implications  for  sustainable  regional  development.  The research  integrates  both  quantitative  and  qualitative  methodologies  to  identify  the economic,  infrastructural,  socio-cultural,  environmental,  and  political  determinants that  shape  regional  tourism  performance.  Findings  indicate  that  infrastructure development, governance efficiency, and community participation significantly affect tourism utilization levels across different regions. The study highlights the importance of strategic planning, environmental sustainability, and local stakeholder engagement in  maximizing  regional  tourism  potential.  The  results  contribute  to  a  deeper understanding  of  how  integrated  policies  and  collaborative  efforts  can  promote equitable and sustainable tourism development within regional contexts.